The effect of intellectual capital on the financial performance of insurance companies listed on the Indonesia Stock Exchange (ISE) - Putri Alif Arifa; Nurmala Ahmar (Universitas Hayam Wuruk Perbanas, 2016)
The purpose of this study is to analyze the effect of Intellectual Capital (VAICTM), with major components of physical capital (VACA), human capital (VAHU), and structural capital (STVA), on financial performance, with indicators of Return on Assets (ROA) and Return on Equity (ROE). Data are taken from 10 insurance com-panies listed on the Indonesia Stock Exchange for four years, 2010-2013. The support-ing data include reference books and journals of previous researches. The data analysis is conducted using Partial Least Square (PLS). The results show that intellectual capital (VAICTM) has significant effect on the financial performance. Physical capital (VACA) and human capital (VAHU) are significant indicators for VAICTM. Mean-while, structural capital (STVA) is not significant. The indicators of financial perfor-mance, both ROA and ROE, are significantly affected by intellectual capital for four years.